A fuzzy logic control system for the rotary dental instruments - Mousavi, Sayedali; Hashemipour, Majid; Sadeghi, Mohsen; Petrofsky, Jerrold Scott; Prowse, Michelle A. (Shiraz University, 2010)
Nickel-titanium alloy (Ni-Ti) rotary dental instrument files are devices which are commonly used in the field of endodontics for root canal preparation. However, Ni-Ti file breakage is common and is often caused by excessive hand pressure by the endodontist during a root canal preparation. The present solution is to automate the control of file failure (caused by pressure) through the development of a fuzzy logic controller to maintain the file breakage. Both in vitro and in vivo experiments were conducted to gather enough data to observe the system behavior and to modify the control system. In vivo results showed that a fuzzy logic control system was able to improve the file life up to 22% compared to existing rotary instrument control systems. Thus the fuzzy logic system presented in this paper not only improves the filing process performance, but reduced the time and costs spent by the endodontist as well through maximizing the use of file life and preventing file failures with the use of an applied intelligent control system. © Shiraz University.
Keywords: Control; Endodontics; File; Fuzzy logic; Ni-Ti